2011
DOI: 10.1007/s00726-011-0890-6
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of a peptidyl-aminoacyl-l/d-isomerase from frog skin

Abstract: In the skin of fire-bellied toads (Bombina species), an aminoacyl-l/d-isomerase activity is present which catalyses the post-translational isomerization of the l- to the d-form of the second residue of its substrate peptides. Previously, this new type of enzyme was studied in some detail and genes potentially coding for similar polypeptides were found to exist in several vertebrate species including man. Here, we present our studies to the substrate specificity of this isomerase using fluorescence-labeled vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…This is consistent with studies of the frog enzyme: substrate specificity studies showed the frog isomerase was able to act upon sequences of only the N-terminus of the peptide. 48 …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with studies of the frog enzyme: substrate specificity studies showed the frog isomerase was able to act upon sequences of only the N-terminus of the peptide. 48 …”
Section: Resultsmentioning
confidence: 99%
“… 9 , 10 Such enzymes have been isolated from frog, 11 spider, 9 , 12 platypus, 13 and sponges. 10 The substrate specificity of the enzymes from frog and platypus has been investigated, showing that they act specifically on the second amino acid from the N-terminus, 13 , 14 whereas the spider enzyme acts on the third residue from the C-terminus. 9 These isomerases have additional disadvantages for synthetic purposes in that they thus far have been isolated from the native organisms and hence have limited supply, and they tend to give a thermodynamic mixture of products.…”
mentioning
confidence: 99%
“…More recent studies on amphibian L/D-isomerases suggested that P. dacnicolor produced PD-3-7 as epimers, which differ by the stereochemical modification, L-Leu2 → d-Leu2 [66]. It is well established that epimeric AMPs are produced by amphibians [5], such as the Polka-dot tree frog, Hypsiboas punctatus [67], which produces phenylseptins.…”
Section: Anti-cancer Other Activities Key Referencesmentioning
confidence: 99%